PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA HASIL PEMBELAJARAN IPAS KELAS V SD NEGERI 32 LUBUKLINGGAU - Messi Intania Putri; Sukasno; Sari Pertiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of social studies students in grade V of SD Negeri 32 Lubuklinggau, which is shown by the fact that there are still many students who have not reached the Learning Goal Achievement Criteria (KKTP). This study aims to determine the extent to which IPAS students in grade V at SD Negeri 32 Lubuklinggau achieve the learning outcomes after implementing the Contextual Teaching and Learning (CTL) model. This study uses a quantitative approach, a pseudo-experiment, and a one-group pretest-posttest design. The population, as well as the research sample, consists of grade V students at SD Negeri 32 Lubuklinggau for the 2025/2026 school year, totaling 24 students, using saturated sampling techniques. Data collection was conducted through learning outcome tests comprising multiple-choice questions, administered before and after the implementation of the CTL learning model. Data analysis techniques include normality tests and z-tests at the α=0,05 confidence level. The results showed an increase in the average score of student learning outcomes from 49.45 in the pre-test to 78.75 in the post-test, as well as an increase in learning completeness from 0% to 87.5%. Thus, it can be concluded that the learning outcomes of the IPAS class V at SD Negeri 32 Lubuklinggau after implementing the Contextual Teaching and Learning (CTL) model are significantly improved. Keywords: Contextual Teaching and Learning, Learning Outcomes, Science.